Pengaruh Penerapan Sistem Akuntansi Keuangan Daerah, Kompetensi Sumber Daya Manusia Dan Peran Audit Internal Terhadap Kualitas Laporan Keuangan Daerah Pada Pemerintah Daerah Kabupaten Tuban - Kartika Sari; Gita Desipradani (UMSurabaya Publishing, 2022)
This study was conducted to determine effect of the application of the regional financial accounting system, Human Resource Competence, Internal Audit Â on the quality regional financial reports in Tuban regional government.This research includes survey research. This research is a popular research. The population in this study were 21 agencies and offices in Tuban Regency as many as 114 people. The data collection technique used is questionnaire. The analysis prerequisite test includes validity and reliability tests as well classical assumption tests which include normality, heteroscedasticity and multicollinearity tests. The data analysis technique used is multiple linear regression analysis. The results of the study indicate the application of the Regional Financial Accounting System has a positive and significant effect on the Quality of Regional Financial Reports in Tuban Regency Government, Regional Human Resource Competence has negative and significant effect on the Quality of Regional Financial Reports in Tuban Regency Government, The role of Internal Audit has positive and insignificant effect on the Quality of Regional Financial Reports in Tuban Regency Government, The application of the regional financial accounting system, the competence of human resources simultaneously has a positive and significant effect on the Quality of Regional Financial Reports in Tuban Regional Government